Empathy and Gesture : The Role of Parents in Understanding Early Childhood - Redi Awal Maulana Maulana; Siti Noor Rochmah; Mutiara Swandhina (SEAMEO CECCEP, 2024)
Every child has the right to express their opinion and be heard. However, not all children have active verbal communication skills. There are also children aged 2-4 years who in their daily lives express their opinions, ideas or desires through messages or non-verbal communication. Gestures are a form of nonverbal communication. Early childhood children use gestures as a way to convey messages so that parents can understand them. Therefore, the role of parents is very important in understanding children's gestures as a form of non-verbal messages. This article aims to illustrate the importance of parents in understanding their children's gestures, so that children feel that their rights are fulfilled. This article is in the form of a literature study from various studies and research which will explain what gestures are, gestures in early childhood and the role of parents in understanding gestures. It is hoped that the results of this article can encourage parents to be more empathetic in listening to children's non-verbal forms of communication, namely gestures. So there will be more effective communication between parents and children.